Comparison between partial ulnar and intercostal nerve transfers for reconstructing elbow flexion in patients with upper brachial plexus injuries - Kakinoki, Ryosuke; Ikeguchi, Ryosuke; Dunkan, Scott FM; Nakayama, Ken; Matsumoto, Taiichi; Ohta, Soichi; Nakamura, Takashi (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
Background There have been several reports that partial ulnar transfer (PUNT) is preferable for reconstructing elbow flexion in patients with upper brachial plexus injuries (BPIs) compared with intercostal nerve transfer (ICNT). The purpose of this study was to compare the recovery of elbow flexion between patients subjected to PUNT and patients subjected to ICNT.Methods Sixteen patients (13 men and three women) with BPIs for whom PUNT (eight patients) or ICNT (eight patients) had been performed to restore elbow flexion function were studied. The time required in obtaining M1, M3 (Medical Research Council scale grades recovery) for elbow flexion and a full range of elbow joint movement against gravity with the wrist and fingers extended maximally and the outcomes of a manual muscle test (MMT) for elbow flexion were examined in both groups.Results There were no significant differences between the PUNT and ICNT groups in terms of the age of patients at the time of surgery or the interval between injury and surgery. There were significantly more injured nerve roots in the ICNT group (mean 3.6) than in the PUNT group (mean 2.1) (P = 0.0006). The times required to obtain grades M1 and M3 in elbow flexion were significantly shorter in the PUNT group than in the ICNT group (P = 0.04 for M1 and P = 0.002 for M3). However, there was no significant difference between the two groups in the time required to obtain full flexion of the elbow joint with maximally extended fingers and wrist or in the final MMT scores for elbow flexion.Conclusions PUNT is technically easy, not associated with significant complications, and provides rapid recovery of the elbow flexion. However, separation of elbow flexion from finger and wrist motions needed more time in the PUNT group than in the ICNT group. Although the final mean MMT score for elbow flexion in the PUNT group was greater than in the ICNT group, no statistically significant difference was found between the two groups.